EVALUATION OF THE USE OF SUSTAINABILITY PRACTICES IN HOTEL MANAGEMENT - CASE STUDY OF IN HOTELS IN NORTHERN COAST OF RS TOWN - Naime, Roberto; Mello, Rita; Huppfer, Haide Maria (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611706325 This paper conducted a study on the theme Sustainability for Environmental Quality in Tourismthrough the diagnosis of responsible environmental practices in the lodging facilities. Weconducted a research and analysis through a case study of a city hotel in the northern coast of RioGrande do Sul to the research instruments were used for data collection and closed directed. Thesurvey was made in analyzing the data that were collected during the months of January andFebruary 2012, through the systematic application of data collection instruments. Thequestionnaire was administered to managers of hotels. The analysis was performed using the datacompiled and interpreted and following an analysis of a "checklist" covering all aspects to beconsidered and analyzed. The results show that it is still very low general awareness by the daily practices of sustainability among both managers and employees of establishments of hotels, andthe guests and customers of these units.